Measuring literacy : performance levels for adults - Hauser, Robert Mason (National Academies Press, 2005)
"Through a process detailed in the book, the committee determined that five performance level categories should be used to characterize adults literacy skills: nonliterate in English, below basic literacy, basic literacy, intermediate literacy, and advanced literacy. This book documents the process the committee used to determine these performance categories, estimates the percentages of adults whose literacy skills fall into each category, recommends ways to communicate about adults literacy skills based on NAAL, and makes suggestions for ways to improve future assessments of adult literacy."--NAP Web site